GREEN ECONOMY: OPPORTUNITIES AND CHALLENGES IN SOUTH EAST ASIA - Ratnadewati, Ainina; Widiastuti, Nur; Wardani, Asri (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This paper aims to explain the concept of a green economy, developments, opportunities, and challenges faced by Southeast Asian countries with implementing a green economy. The data used in this research is secondary data obtained from various sources, including the United Nations Environment Program (UNEP), OECD, BAPPENAS, and other sources. The analytical method used is a qualitative descriptive method. The results show that ASEAN countries have enormous opportunities because SEA has favorable demographics and a rapidly growing middle class. 380M residents (~60% of the total population) are under 35. Above-average growth of 4% annual nominal GDP growth over the past decade. Each country has unique advantages and roles to play in the global economy. And the World's 11th largest car manufacturer, with the potential to become an Electric Vehicle (EV). Facing challenges in terms of making decarbonization in terms of dependence on fossil fuels, conditions as a developing country, efforts to balance decarbonization and growth as an island country facing connectivity constraints, the large number of workers working in the fossil fuel sector, and resource imbalances that can be renewed. Recommended actions: Build capacity for better enforcement of existing conservation policies, Incentivize the restoration/protection of forestlands vs. new land clearing for plantations, and Incentivize mangrove and peatland restoration/protection at scale. As an island country, efforts to balance decarbonization and growth face connectivity constraints, the large number of workers working in the fossil fuel sector, and inequality in renewable resources. Recommended actions: Build capacity for better enforcement of existing conservation policies, Incentivize the restoration/protection of forestlands vs. new land clearing for plantations, and Incentivize mangrove and peatland restoration/protection at scale. As an island country, efforts to balance decarbonization and growth face connectivity constraints, the large number of workers working in the fossil fuel sector, and inequality in renewable resources. Recommended actions: Build capacity for better enforcement of existing conservation policies, Incentivize the restoration/protection of forestlands vs. new land clearing for plantations, and Incentivize mangrove and peatland restoration/protection at scale. Incentivize the restoration/protection of forestlands vs. new land clearing for plantations—Incentivize mangrove and peatland restoration/protection at scale. Incentivize the restoration/protection of forestlands vs. new land clearing for plantations—Incentivize mangrove and peatland restoration/protection at scale.